Proposed new interior design fashion boutique for Bernard Chandran at A-07-G, A-07-01, 07-02 & 07-03 Neo Damansara, Damansara Perdana, 48300 Petaling Jaya, Selangor / Irna Izyani Moho Azhari - Moho Azhari, Irna Izyani (Faculty of Architecture, Planning and Surveying, 2010)
Each and every final year, students are required to prepare themselves with a final year project. It is cumpolsary and with their new, bright, and fresh ideas, students will get their chance to design and explore their proposed project. The proposed project written in here will be, a new interior design boutique for Bernard Chandran at A-07-G, A-07-01, 07-02 & 07-03 Neo Damansara, Damansara Perdana, 48300 Petaling Jaya, Selangor. Dato’ Bernard Chandran, is a successful fashion designer and is now entitled as the ‘Kind Of Fashion’ in Malaysia. Chandran was certainly a mixed bag. Fluid lines in soft, sheer fabrics made their way down the runway alongside familiarly structured pieces, identifying the broad spectrum of influences behind Chandran’s designs. In a backstage chat with MFL, the designer revealed that he gathers inspiration wherever he travels and likes to inject his own feminine glamour into traditional designs. Indeed, there was a definite nod to Chandran’s South East Asian origins with the adapted conical hat, block-heeled shoes, and simple bamboo print that kicked-off the impressive show. It appears that Chandran’s inspiration however, does not just lie in these exotic locations which have undoubtedly led to some of the most outlandish designs within his Spring 2010 collection. While the opulent yet slightly menacing masks, which aocentuate Chandran’s love of the human form together with constructed outer corsets, are immediate products of Chandran’s travel; the muted tones and symmetrical shapes of some of the mini dresses are inspired simply by his constant surroundings in the designer workshop. In this report, the whole new look and image of Bernard Chandran are proposed structurally according to the design process and material presented. This proposal which reflects the whole new look of Bernard Chandran’s new boutique covers every space departments. The concept ‘flawless’ is basically in a perfectly built design, so that the interior is structured.